Hydroxylation at Multiple Positions Initiated the Biodegradation of Indeno[1,2,3-cd]Pyrene in Rhodococcus aetherivorans IcdP1 - Miao, Li-Li; Qu, Jie; Liu, Zhi-Pei (Frontiers in Microbiology, 2020)
Biodegradation of polycyclic aromatic hydrocarbons with six or more rings, such as indeno[1,2,3-cd]pyrene (IcdP) was rarely described. An IcdP-degrading strain, Rhodococcus aetherivorans IcdP1, was isolated from contaminated soil. It could grow on and efficiently degrade various HWM PAHs, such as IcdP, benzo[a]pyrene and benzo[j]fluoranthene. It showed highest degrading ability towards IcdP (>70% within 10 days). The IcdP degradation was initiated by ring hydroxylation with multiple pathways, including the hydroxylation at 1, 2 and 7, 8 positions, according to the relevant metabolites detected, e.g. cyclopenta[cd]pyrene-3,4-dicarboxylic acid, 2, 3-dimethoxy-2, 3-dihydrofluoranthene. The transcriptional patterns of the genes encoding ring-hydroxylating oxygenases (RHOs) and cytochrome P450 monooxygenases (CYP450s) under the induction of IcdP, pyrene and benzo [b] fluoranthene (BbF), were compared to determine the key initial ring-hydroxylating oxygenases in the conversion of IcdP. The expression of RHOs 1892-1894, 1917-1920 and 4740-4741 was induced strictly by IcdP, and the amino acid sequences of these proteins showed very low identities with their homologues. These results suggested that IcdP was degraded through dioxygenation-initiated metabolism pattern, and RHOs 1892-1894, 1917-1920 and 4740-4741 responded for the initial ring cleavage of IcdP through 1, 2-dihydrodiol or 7, 8-dihydrodiol. The studies would contribute to the understanding of the molecular mechanism of initial degradation of IcdP.